Estudo sobre amplificadores híbridos RAMAN e EDFA - Benincà, Matheus Oggioni Lima (2012)
This work presents a study on hybrid optical amplifiers EDFA and Raman. Individual concepts are defined such as operation mode, gain and noise. While operanting as a group the HA has been classified by their gain composition and the operation modes of each amplifier. The simulation code basis for this amplifiers are also presented with an user guide interface for Raman amplifiers. This GUI allows the optimization of the wavelenght and power of the Raman laser pumps. It can plot the gain grafics and ripple and allows differente types of fiber and combination of signals to be simulated. It is presented a case of study of a WDM link that has an EDFA and uses the spectral flexibility of the Raman gain for a HA with seamless wideband. Using 40 WDM channels spread on 65 nm of bandwidth on C and L band having 2 db of ripple and operating on 90 km, 120 km, 150 km and 180 km of single mode fiber. This works complents the study on hybrid amplifiers and presents one of it‘s aplications with results of gain, OSNR, NF and ripple.